Sustainable Mobility In the city Of Bratislava – Tram Priority - Fischer, Jan (Communications - Scientific letters of the University of Zilina, 2013)
United Nations Development Programme (UNDP), acting as an implementing agency of the Global Environment Facility (GEF) implemented the project “Sustainable Mobility in the City of Bratislava”. One component of the project deals with a higher level of priority to Bratislava‘s trams. Driving time information from the ITCS of Bratislava public transport operator was evaluated with Hamburg-Consults software “planfahrt” in order to find obstacles responsible for slowing down tram operation. Thereafter measures based on best practice solutions were introduced for a fast and reliable tram operation: “The tram stops at stations only”. Integral part was the simulation of public transport priority at three signalized intersections using transport modelling software “ptv VISSIM”. The results prove the effectiveness of the priority. Public transport waiting times are reduced; the reliability of public transport operations improves.